Hypertrophic Ecosystems 1980
DOI: 10.1007/978-94-009-9203-0_12
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Trophic-Level Interactions to the Abundance and Species Composition of Algae in Lakes

Abstract: The thesis is presented that the quantitative and qualitative responses of water bodies to nutrient inputs are affected greatly by the structures of their biotic communities. Evidence is given to show that in addition to the thesis being correct intuitively, it can be supported by field experiments and by observations even on such well-known lakes as L. Washington, L. Norrviken, L. Trummen, and L. Mendota. Emphasis is on the roles of herbivorous zooplankters in controlling algal blooms and their apparent capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 22 publications
1
73
0
1
Order By: Relevance
“…The population of the phytoplankton is dependent upon the population of the zooplankton, as zooplankton grazing was identified as a strong modulator of the phytoplankton yield in lakes and reservoirs [62]. The results from the present study showed a pattern of low or inverse correlation between phytoplankton and zooplankton population density.…”
Section: Canonical Correlation Analysis (Cca)supporting
confidence: 49%
“…The population of the phytoplankton is dependent upon the population of the zooplankton, as zooplankton grazing was identified as a strong modulator of the phytoplankton yield in lakes and reservoirs [62]. The results from the present study showed a pattern of low or inverse correlation between phytoplankton and zooplankton population density.…”
Section: Canonical Correlation Analysis (Cca)supporting
confidence: 49%
“…However, progressive recognition of ecological-biotic interactions spawned partly from long-term studies of Lake Washington (Edmondson and Litt, 1982;Edmondson, 1994;Edmondson et al, 2003), and thereafter in a range of shallow lakes in several densely populated lowland nations in Europe (e.g. Gulati et al, 1990;Moss, 1999;Kairesalo and Vakkilainen, 2004) brought widespread recognition to Shapiro's (1980) now familiar concept of food web or biomanipulation -schematically illustrated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Benndorf et al 1984;Schoenberg and Carlson 1984; McQueen et al. 1986;Post and McQueen 1987) the biomass of algae (Shapiro 1980;Henssen et al 1986), water clarity (Shapiro and Wright 1984), and total phosphorus (Wright and Shapiro 1984). A few studies have also considered the combined effects of fertilization and fish addition on algal biomass (e.g.…”
mentioning
confidence: 99%